The Inhibition of Autophagy Sensitises Colon Cancer Cells with Wild-Type p53 but Not Mutant p53 to Topotecan Treatment - Li, Dan-Dan (Public Library of Science, 2012)
BACKGROUND: Topotecan produces DNA damage that induces autophagy in cancer cells. In this study, sensitising topotecan to colon cancer cells with different P53 status via modulation of autophagy was examined. METHODOLOGY/PRINCIPAL FINDINGS: The DNA damage induced by topotecan treatment resulted in cytoprotective autophagy in colon cancer cells with wild-type p53. However, in cells with mutant p53 or p53 knockout, treatment with topotecan induced autophagy-associated cell death. In wild-type p53 colon cancer cells, topotecan treatment activated p53, upregulated the expression of sestrin 2, induced the phosphorylation of the AMPKα subunit at Thr172, and inhibited the mTORC1 pathway. Furthermore, the inhibition of autophagy enhanced the anti-tumour effect of topotecan treatment in wild-type p53 colon cancer cells but alleviated the anti-tumour effect of topotecan treatment in p53 knockout cells in vivo. CONCLUSIONS/SIGNIFICANCE: These results imply that the wild-type p53-dependent induction of cytoprotective autophagy is one of the cellular responses that determines the cellular sensitivity to the DNA-damaging drug topotecan. Therefore, our study provides a potential therapeutic strategy that utilises a combination of DNA-damaging agents and autophagy inhibitors for the treatment of colon cancer with wild-type p53.